Negative Effects of Entrepreneurship : Coping with burnout and anxiety among Slovak family business owners - Jákli, Viktória (2024)
The objective of this qualitative study is to examine the challenges of entrepreneurship by reviewing the perspectives of Slovak family business owners. The purpose of the study is to identify the extent to which these business owners take care of their mental health, specifically regarding anxiety and burnout syndrome. Through ten in-depth interviews, the study seeks to determine whether Slovak family business owners address and actively implement strategies for controlling and mitigating the negative effects of entrepreneurship on their well-being. The central research question revolves around the awareness and acknowledgment of mental health challenges among these entrepreneurs and the efficacy of coping techniques utilized in case of dealing with anxiety or burnout syndrome. The objective of the research is to identify coping strategy trends and determine whether people take proactive steps or tend to ignore their mental health, particularly burnout syndrome and anxiety. The study also explores environmental and cultural factors that can affect these business owners' mental health attitudes by exploring their narratives. It is expected that the results of this study will contribute insights to academic research as well as have real-world applications for family business owners' welfare. The investigation of coping strategies and mental health behaviors among Slovak business owners will highlight the necessity of specialized support networks and interventions in the setting of family enterprises. The study's ultimate goal is to provide information that could support a better work-life balance and improve the mental health care of business owners in Slovakia.